REDUCING AGGRESSIVE BEHAVIOR USING SOLUTION-FOCUSED BRIEF COUNSELING (SFBC) - Fifi Khoirul Fitriyah (JBKI (Jurnal Bimbingan Konseling Indonesia), 2017)
The purpose of this study was to test the effectiveness of Solution-Focused Brief Counseling (SFBC) in reducing students’ aggressive behavior in Tuban District, East Java. The research approach is quantitative by using experiment with single subject research type AB. Data analysis uses descriptive statistics. The results of preleminary study toward 162 students showed that 30 students (19%) were in high category, while in the low category was 26 students (16%). Empirical test explained that SFBC had shown efective to reduce aggressive behavior in four students in all aspects. In the other hand, two students others did not reduce in verbal aggression aspects.